Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1128/jvi.00822-06
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Bunyamwera Orthobunyavirus NSs Protein with Mediator Protein MED8: a Mechanism for Inhibiting the Interferon Response

Abstract: The NSs protein of Bunyamwera virus (Bunyaviridae) is an antiapoptotic interferon antagonist involved in silencing host protein expression by interfering with mRNA synthesis. Here, we show that the ability to inhibit both host transcription and the interferon response is linked to interaction of NSs with the MED8 component of Mediator, a protein complex necessary for mRNA production. The interacting domain on NSs was mapped to the C-terminal region, which contains amino acids conserved among orthobunyavirus NS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 52 publications
1
93
0
Order By: Relevance
“…Control RT-PCRs for the LACV N gene showed that viruses replicated to comparable levels, and RT-PCRs for the cellular ␤-actin mRNA demonstrated that all preparations contained similar amounts of RNA. Of note, RT-PCR analysis for some RNA polymerase II-dependent, constitutively expressed cellular genes shows a strong reduction in wt-infected cells (6), supporting the view that LACV NSs may influence cellular transcription in a manner similar to BUNV NSs and RVFV (32,33,51).…”
Section: Inhibition Of Ifn Induction In Fibroblastsmentioning
confidence: 68%
“…Control RT-PCRs for the LACV N gene showed that viruses replicated to comparable levels, and RT-PCRs for the cellular ␤-actin mRNA demonstrated that all preparations contained similar amounts of RNA. Of note, RT-PCR analysis for some RNA polymerase II-dependent, constitutively expressed cellular genes shows a strong reduction in wt-infected cells (6), supporting the view that LACV NSs may influence cellular transcription in a manner similar to BUNV NSs and RVFV (32,33,51).…”
Section: Inhibition Of Ifn Induction In Fibroblastsmentioning
confidence: 68%
“…Previous results have shown that TOSV activates transcription of IFN-␤ during infection, in contrast to that observed for other members of the Bunyaviridae family (9). In fact, many of these viruses possess the nonstructural protein NSs, which counteracts IFN-␤ production, resulting in viral escape from the host immune response (15,17,20,(24)(25)(26)(27)(28)(29). To better address the mechanisms which regulate IFN-␤ production in TOSV infection, the role of RIG-I was investigated.…”
Section: Resultsmentioning
confidence: 99%
“…LACV NSs does not interact with MED 8 or p44 (data not shown), the host cell factors mediating RNAP II inhibition by the NSs proteins of BUNV and RVFV, respectively (23,58). Moreover, unlike what was shown for herpes simplex virus (75), a dominant-negative form of HSC70 cannot rescue RNAP IIo degradation by LACV infection (data not shown).…”
Section: Discussionmentioning
confidence: 84%
“…Both these viruses encode NSs proteins, which, although being different in sequence, size, and mode of expression, act on the level of general host cell transcription. BUNV (which is closely related to LACV) expresses an NSs, which interferes with the phosphorylation on CTD-Ser-2 (25) and interacts with MED8, a component of the Mediator transcription complex (58). The Mediator complex is involved in RNAP II regulation (59) and contacts the CTD-Ser-2 kinase P-TEFb (60).…”
Section: Discussionmentioning
confidence: 99%